Housing Score : Its Correlation With Morbidity Profile - Bansal R.K; Saxena D.M; Sharma V (Wolters Kluwer Medknow Publications, 1992)
Various studies have focused attention on the relationship between housing and health and have established residential environment as an important determinant of the health status of its residents. However, there is a paucity of research work on the development and assessment of comprehensive and quantifiable housing scores and their correlation with the general morbidity profile of residents. Such mathematical housing assessment scores may provide a valuable foresight to city and health planners. In the present study, 2,536 individuals from 542 families, residing in 5 different types of houses were analysed. The residential environment was quantified by using a scoring system developed by Desai and the families were grouped into 3 categories accordingly. A complete health check up of all residents was undertaken to ascertain their disease profile. It was observed that high housing scores were significantly associated with an increase in non- communicable diseases and diseases of the nervous and respiratory systems, while low scores had a high prevalence of communicable, infectious and parasitic diseases. The findings were validated by a repeat assessment using individual parameters separately.